Deep vein thrombosis associated with Staphylococcus aureus septicemia - Peninnah Oberdorfer (Faculty of Medicine, Chiang Mai University, 2019)
Chiang Mai Medical Journal (Formerly Chiang Mai Medical Bulletin) is an official journal of the Faculty of Medicine, Chiang Mai University. It accepts original papers on clinical and experimental research that are pertinent in the biomedical sciences. The Journal is published 4 issues/year (i.e., Mar, Jun, Sep, and Dec).